Teknik Neuro Linguistic Program Dalam Pendidikan Tauhid Rasulullah Saw - Rahmat Lutfi Guefara; Robingun Suyud El Syam (STIKes Ibnu Sina Ajibarang, 2023)
The Prophet was a role model in various ways, so it is interesting to know his strategy for teaching monotheism to his friends. This article includes literature research that is qualitative-descriptive, using the primary source Politikus Sittah and related reference secondary data, collected using random sampling techniques, analyzed: reduction, interpretation, comparison, and reflection. The research concludes: through searching several hadiths, it can be found that Rasulullah used the NLP method in educating his friends regarding monotheism material. NLP in the form of building closeness using the Pacing technique, namely how students follow the body movements made by the educator to equalize brain waves, where the body, thoughts and feelings are one unit. If thoughts and feelings are united, then there will definitely be a match so that whatever is said by both parties can be accepted directly by the subconscious mind without having to be criticized first by the conscious mind. In this way, what the Prophet hoped would reach the students, namely the Prophet's friends.